Optical rotatory dispersion of mucopolysaccharides IV. Optical rotatory dispersion and circular dichroism of glycosaminoglycans and heparan sulfate fractions from the urine of patients with mucopolysaccharidosis (Hurler Syndrome) - Stone, Audrey L.; Constantopoulos, George; Sotsky, Stuart M.; Dekaban, Anatole (Biochimica et biophysica acta, 1970)
Genetic defects in the Hurler syndrome lead to the excessive accumulation of dermatan and heparan sulfate in many tissues and to the increase in excretion of these compounds in the urine. Patients exhibit mental detorioration, dwarfism, hepatosplenomegaly, corneal opacities and skeletal deformities. Acid mucopolysaccarides derived from the urine of heparan sulfate excretors (the Sanfilippo variant) and from mixed, dermatan sulfate and heparan sulfate excretors (the Hurler variant) were investigated. Molecular weight distributions by gel filtration and carbazole-orcinol (C/O) reactivities of the samples gave an average molecular weight of about one-third of normal for the Sanfilippo heparan sulfate which could be further separated into two fractions differing in molecular weight, sulfate content and primary structure. Optical absorption and rotary properties (from 250 to 185 mμ) of these glycosaminoglycans were studied to examine the conformational features of the accumulating substances. The results for the Sanfilippo heparan sulfate fractions indicate that two distinct heparin sulfates accumulate in this genetic defect, one with conformational structure essentially like that found in normal tissue but low in O-sulfate, and the other with heparin-like conformation and high N-sulfate content. The ultraviolet optical rotatory dispersion and circular dichroism of dermatan sulfate are greatly different from that of heparan sulfate, providing an optical method of distinguishing among Sanfilippo and other Hurler variants.